History of the Working Classes in France: Renaissance and Modern Period - Wergeland, A. M. (Journal of Political Economy, 1904)
M. LEVASSEUR'S second volume' is, if possible, even more enjoyable and suggestive than the first. Several leading economists called his work, when it appeared in its first edition, a model of acculracy. The present edition deserves this praise even more absolutely. The material on which M. Levasseur bases his presentation of the vicissitudes of industry and the laboring classes is in every respect excellent and amply jtustifies his views. If the reviewer, while examii]ing the wealth of illustration contained in the first volume, felt conmpelled to keep in abeyance any dissenting opinion of his, he feels still more so as he penetrates into the contents of the second volhme. with its vast storelhouse of information and the careful investigation on which it rests. The following pages will be, as before, an attempt to give the general reader and the student an idesq of the interesting contents of the volume. M. Levasseur in hiis work goes as much as possible into detail, and repeats himself frequently in an endeavor to be perfectly clear and simple. Our review is but a rapid summary of the most prominent features of thils importanit production, and has sufficiently served its purpose if it induces students to examine the volume for themselves. Wlihen the French crossed the Alps in I494, M. Levasseur tells US, they found in Italy manners more elegant than theirs, a refinement of civilization unknown to the North. Italy was to them like the discovery of a new world. It was then the richest country in Europe. Lombardy resembledl a garden; in the cities large numbers of the inhabitants were busy with industry and trade. Silk goods, gold and silver brocade. glass, fayence, perfumery, and other luxuries were fabricated tlhere. The satins and velvets of Venice and Genoa, the fayence of Bologna and of Urbino, the jewelry of Florence, Rome, and Venice, the glassblowers of Murano, were all renowned. Italy had become the international market of two worlds, and the general prosperity and the rivalry between